Apothecial anatomy of some species of Heterodermia of Namobudha - Rajbhandary, Sangeeta; Thapa, Khem B (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.119-123